2018
DOI: 10.25103/jestr.116.19
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Calcium Chloride Dehydrate as Stabilizing Agent for Expansive Soil

Abstract: The effectiveness of stabilizing expansive soil by enhancing its geotechnical properties using calcium chloride dehydrate (CaCl 2 .2H 2 O) as a soil stabilizing agent was investigated in this research. The chemical treatment process using calcium chloride elaborates carrying out experimental laboratory tests on an expansive soil taken from eastern side of Irbid city (Jordan) to check the influence of calcium chloride on its geotechnical engineering properties. Calcium chloride (CaCl 2) was added as a solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A few examinations have been made on soil stabilization utilizing distinctive stabilizing agents. Sharo et al [6] demonstrated the adequacy of the expansion of calcium chloride in soil treatment. Amhadi and Assaf [7] utilized calcium oxide as a stabilization technique in clay soils so as to restrain its development contraction properties.…”
Section: Introductionmentioning
confidence: 99%
“…A few examinations have been made on soil stabilization utilizing distinctive stabilizing agents. Sharo et al [6] demonstrated the adequacy of the expansion of calcium chloride in soil treatment. Amhadi and Assaf [7] utilized calcium oxide as a stabilization technique in clay soils so as to restrain its development contraction properties.…”
Section: Introductionmentioning
confidence: 99%